An investigation into the forces shaping the evolution of global shipping alliances - Ju, Huizhu; Zeng, Qingcheng; Haralambides, Hercules; Li, Yimeng (Maritime policy and management, 2024)
Global shipping alliances have become an important institution in international seaborne trade. Their raison d'être is higher efficiency and lower costs, to the benefit of the consumer. However, experiences from GSA operations during the COVID-19 supply chain crisis show that GSAs may have considerable market power, not quite aligned with the spirit of the lawmaker who has exempted them from antitrust laws. This raises many questions this paper attempts to answer: What drives the formation, stability and dissolution of GSAs? And have external and internal factors, such as government policies, ship sizes and freight rates, had always the same effect on GSAs over time? We decompose industry concentration (HHI) into seven components. This is done based on the Variational Mode Decomposition model. The components are subsequently reconstructed through gray correlation. Next, a Generalized Additive Model is specified, to analyze the relationships between influencing factors and the evolution of GSAs. We look both at the development (trend) of industry concentration, as well as its fluctuations (cyclicality) over time. We show that effects vary over time, with the same factors having different impacts on GSAs at different times. The paper can assist policymakers in their efforts to regulate and supervise container shipping.